Efecto del uso de Saccharomyces cerevisiae bajo condiciones fermentativas en la calidad de taza del café (Coffea arabica L.) en el cantón Loja - Martinez Cumbicus, Marjorie Lizbeth (2021)
The research was carried out in coffee farms located in Malacatos, Vilcabamba and Loja (Ecuador), with the objective of determining the effect of the use of Saccharomyces cerevisiae under fermentative conditions on the cup quality of coffee (Coffea arabica L.). The behavior of 20 ml of commercial Saccharomyces cerevisiae in the aerobic and anaerobic fermentation of coffee with natural and washed processing was evaluated, using different varieties of coffee in each farm, Colombia variety in the farm "El Aguacate", Nestlé Hybrid in the farm "Nuestro Refugio" and in "Doña Julita" the Bourbon variety was used. In each type of fermentation, the initial, intermediate and final pH and Brix degrees (°Bx) were measured as a function of time; the coffee was dried in canopies prior to direct exposure to the sun to avoid the proliferation of fungi. In addition, a sensory analysis was carried out with two certified tasters who evaluated the organoleptic characteristics of the coffee: fragrance/aroma, flavor, body, acidity, uniformity, clean cup, and cupper's score; as well as determining the primary and secondary defects. The results indicate that the decrease in pH and °Bx depend on the climatic conditions of the location, variety, time and type of fermentation. The addition of Sacharomyces cerevisiae significantly influenced cup quality scores within each farm, categorizing them as specialty coffees. The Nestlé Hybrid located between 1 950 and 2 060 msnm obtained a score of 87.86 in an aerobic fermentation with natural coffee, Bourbon located at 1 593 msnm was scored with 86.63 in an aerobic fermentation with natural coffee and Colombia the best score was 86.75 with an anaerobic fermentation in natural coffee. Key words: Saccharomyces cerevisiae, aerobic fermentation, anaerobic fermentation, drying, medium roasting, tasting.